Scolecite as an efficient heterogeneous catalyst for the synthesis of 2,4,5-triarylimidazoles - Gadekar, Lakshman S.; Mane, Shivshankar R.; Katkar, Santosh S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2009)
Natural scolecite has been found as an effective catalyst for the one-pot synthesis of 2,4,5-triarylimidazole derivatives via a three component reaction using benzil or benzoin, aldehydes and ammonium acetate. This method provides several advantages such as being environmentally benign, reusable, possessing high yields with increased variations of the substituents in the product and preparative simplicity.
Keywords: 2; 4; 5-Triarylimidazoles; heterogeneous catalyst; Three-component reaction

Scolecite catalyzed facile and efficient synthesis of polyhydroquinoline derivatives through hantzsch multi-component condensation - Gadekar, Lakshman S.; Katkar, Santosh S.; Mane, Shivshankar R.; Arbad, Balasaheb R.; Lande, Machhindra K. (Bulletin of the Korean Chemical Society, 2009)
A facile and efficient synthetic route has been developed for the polyhydroquinoline via four component reactions of aldehydes, dimedone, ethyl acetoacetate and ammonium acetate in the presence of catalytic amount of scolecite in ethanol at 70 degrees C through Hantzsch reaction. This method gives remarkable advantages such as simple work-up procedure. environmentally friendly, inexpensive, non-toxic and recyclable catalyst, shorter reaction time along with excellent yields
Keywords: heterogeneous catalyst; Multicomponent reaction; Polyhydroquinoline; Reusable catalyst

Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond